“Life we must accept as we see it” – A critical Reading of Joyce’s “Drama and Life” - Cruz, Tarso do Amaral de Souza (ABEI Journal, 2019)
James Joyce’s fictional works have been vastly analyzed and discussed ever since the first decades of the twentieth century. Nevertheless, only recently there has been a consistent growth of the critical attention given to Joyce’s essayistic production. One of the most emblematic essays written by Joyce is “Drama and Life”, from 1900. It is precisely in this essay that Joyce introduces and develops concepts – such as Joyce’s concept of drama – that would eventually turn out to be of paramount importance to the unfolding and to the understanding of his work as a whole. This article aims to critically analyze “Drama and Life” and hopefully provide enough evidence to support the hypotheses that Joyce’s conceptualization of drama is based upon basically essentialist premises and that these very premises have foundational importance for the development Joyce’s fictional work.  The ideas on Joyce’s essayistic output, as well as on “Drama and Life” itself, posited by Caetano W. Galindo, Richard Ellmann, Sérgio Medeiros, and Andrew Gibson are used as theoretical basis for the development of the article.